Protective Effect of Panax quinquefolium Against Chemical-Induced Gastric Mucosal Injury - Hsu, Cheng-Chen; Chen, Fu-An; Su, Borcherng; Lin, Li-Chin; Matsui, Hirofumi; Hsu, Mei-Chich (Asian Journal of Chemistry, 2011)
The American ginseng (Panax quinquefolium L.) is widely used in the oriental traditional medicine. The present study investigates the protection effects of Panax quinquefolium extract granule (PQEG) against chemical-induced gastric mucosal injury. In vitro cell damage was induced by incubating rat gastric mucosal cells, RGM1, with indomethacin (INDO) and quantitated by methylthiazole-tetrazolium (MTT) assay. In vivo gastric damage was induced by 70 % ethanol 10 mL/kg and the ulcer index was calculated the gastric mucosal damage percentage. In vitro study, Panax quinquefolium extract granule revealed significant protection on rat gastric mucosal cells, RGM1, from indomethacin-caused cytotoxicity, with an EC50 of 694.4 mg/kg (95 % CL: 582.2-872.6). In vivo studies showed pretreatment with Panax quinquefolium extract granule caused a significant and dose-dependent inhibition of ethanol-induced gastric mucosal damage, with an ED50 of 588.7 mg/kg (95 % CL: 426.8-850.3). In conclusion, Panax quinquefolium treatment shows protective role in indomethacin-induced gastric mucosa cell injury in vitro and ethanol-induced gastric mucosa lesions in vivo.